INTEGRATION OF CODING AND AI IN ISLAMIC EDUCATION CURRICULUM MANAGEMENT: A CONCEPTUAL STUDY - Ghozali, Achmad Fais; Jasri, Moh.; Syafiih, M. (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This paper aims to explore the integration of programming (coding) and artificial intelligence (AI) in the management of Islamic education curriculum, with a focus on maintaining traditional Islamic values. This paper uses a conceptual approach to develop a theoretical understanding of how technology can be applied in Islamic education without ignoring religious principles. The results of the study indicate that coding and AI have great potential in improving the quality of teaching, accessibility of education, and supporting independent learning. In the context of Islamic education, this technology can be used to enrich the learning experience, such as the development of AI-based Al-Quran learning applications and coding-based interactive teaching applications. The integration of coding and AI in the Islamic education curriculum should be carried out through a holistic planning process, which includes identifying needs, integrating technology into curriculum content, and designing lessons that are in line with Islamic values. Therefore, technology not only increases the effectiveness of learning but also helps shape students' character in accordance with Islamic teachings. This paper provides recommendations for developing a curriculum that combines technology with Islamic principles, making it relevant to the development of the times while maintaining the spiritual aspect of education.Keywords: Artificial Intelligent, Coding, Curriculum Management, Islamic Education